An Analysis of Surf & Turf Experiences of Tourists from Different Nations in Turkey from The Sustainable Gastronomy Tourism Perspective – Farklı Milletlerden Turistlerin Türkiye’deki Surf &Turf Deneyimlerinin Sürdürülebilir Gastronomi Turizmi Perspektifin - Gürkan Akdağ (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
As tourism developed throughout the world, tourism types which may be counted as alternatives to mass tourism have developed in national and international levels and different touristic experiences and investigated in the literature every day. One of the alternative tourism types that is significant for the creation of a sustainable tourism climate, gastronomy tourism recently became a popular type of tourism due to the increase in individuals’ income and their intellectual level. The increase in the number of tourists who solely travel for gastronomical pleasures today demonstrates the potential of the related type of tourism in the near future. The objective of the present study is to analyze the new alternative for sustainable gastronomy tourism, the food experience of surf and turf from the perspective of tourists visiting Turkey. This study, conducted in qualitative research design, consists of the views of 14 tourists visiting Turkey from different countries on their surf and turf experiences. Findings demonstrated that the gastronomy tourists did not know such a cuisine experience existed in Turkey, and stated that the presentations were generally impeccable and Turkish kitchen, known with red meat dishes, should be promoted with its seafood cuisine as well.